2018
DOI: 10.1080/08820139.2018.1423571
|View full text |Cite
|
Sign up to set email alerts
|

Association of increased eomesodermin, BCL6, and granzyme B expression with major clinical manifestations of Hashimoto’s thyroiditis – an observational study

Abstract: Our exploratory results suggest a role for GZMB, EOMES, and BCL6 in the context of HT, thyroid injury, and aggressive/advanced disease forms. Functions enriched within differentially expressed transcripts could be an important new target in understanding the pathogenesis of HT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…CD4 + T cells are also known to show cytotoxic phenotypes in some conditions, including chronic viral infections (13,14), and some tumors, including malignant melanoma (15) and multiple myeloma (16). It has been reported that cytotoxic CD4 + T cells expressing perforin (a cytotoxic molecule) infiltrated into thyroid glands in patients with Hashimoto thyroiditis (17), and that the expression of another cytotoxic molecule, granzyme B, in peripheral T cells was higher in patients with Hashimoto thyroiditis than in T cells isolated from healthy controls (18). However, it remains unclear if CD4 + T cells are present in the involved organs in irAE or if they exhibit any cytotoxic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…CD4 + T cells are also known to show cytotoxic phenotypes in some conditions, including chronic viral infections (13,14), and some tumors, including malignant melanoma (15) and multiple myeloma (16). It has been reported that cytotoxic CD4 + T cells expressing perforin (a cytotoxic molecule) infiltrated into thyroid glands in patients with Hashimoto thyroiditis (17), and that the expression of another cytotoxic molecule, granzyme B, in peripheral T cells was higher in patients with Hashimoto thyroiditis than in T cells isolated from healthy controls (18). However, it remains unclear if CD4 + T cells are present in the involved organs in irAE or if they exhibit any cytotoxic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The main pathological features include lymphocytic infiltration in germinal centers, diffuse enlargement of the thyroid gland, destruction and atrophy of thyrocytes, and interstitial fibrosis. The serological feature is persistent positivity of thyroid autoantibodies including thyroglobulin antibody (TGAb) and thyroid peroxidase antibody (TPOAb) 4, 5. The pathogenesis of HT depends on many elements, including genetic predisposition, environmental implication, and immunological factors.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous papers revealed that decidual CD8 + T cells of healthy pregnant women do not express GZMB and PRF1 ( 80 , 81 ). However, GZMB was overrepresented in peripheral blood T cells from HT patients and its levels varied by age, thyroid volume, and disease severity ( 82 ). Elevated GZMB in preeclampsia inhibits invasion and migration of trophoblasts ( 83 ).…”
Section: Discussionmentioning
confidence: 99%